2015
DOI: 10.1111/jam.12763
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Ralstonia solanacearum -infecting bacteriophages from tomato fields in Chiang Mai, Thailand, and their experimental use as biocontrol agents

Abstract: Aims: To isolate and characterize novel bacteriophages infecting the phytopathogen, Ralstonia solanacearum, and to evaluate them as resources with potential uses in the biocontrol of bacterial wilt. Methods and Results: Fourteen phages infecting R. solanacearum were isolated from soil samples collected in Chiang Mai, Thailand. The phages showed different host ranges when tested against 59 R. solanacearum strains isolated from Thailand and Japan. These phages were characterized as nine podoviruses and five myov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 27 publications
0
33
0
2
Order By: Relevance
“…Bacteria were cultured in CPG medium containing 0.1% (w/v) casamino acids, 1.0% (w/v) peptone, and 0.5% (w/v) glucose (Horita and Tsuchiya, 2002) at 28°C with shaking at 200–300 rpm. Bacteriophages ΦRP12 and ΦRP31 were isolated from tomato fields in Chiang Mai, Thailand as described previously (Bhunchoth et al, 2015). Each phage was routinely propagated using R. solanacearum strain MAFF 730138 as the host.…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria were cultured in CPG medium containing 0.1% (w/v) casamino acids, 1.0% (w/v) peptone, and 0.5% (w/v) glucose (Horita and Tsuchiya, 2002) at 28°C with shaking at 200–300 rpm. Bacteriophages ΦRP12 and ΦRP31 were isolated from tomato fields in Chiang Mai, Thailand as described previously (Bhunchoth et al, 2015). Each phage was routinely propagated using R. solanacearum strain MAFF 730138 as the host.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, larger viruses have been isolated, and their discovery has greatly enriched our understanding of biological entity diversity and evolution (Bhunchoth et al, 2015; Sharma et al, 2015). Jumbo phages have been isolated from diverse niches and exhibit extremely high genetic diversity.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Subsequently, the characterization of 14 bacteriophages isolated from soil in Thailand, belonging to the Podoviridae and Myoviridae families, revealed that the combination of two podoviruses (J2 and φRSB2) efficiently lysed R. solanacearum cells in contaminated soil but, only J2 treatment prevented disease development in tomato plants (Bhunchoth et al, 2015) ( Table 1 ). The application of mixtures of other six lytic bacteriophages, isolated from soil in Sri Lanka, to the rhizosphere of tomato plants as a soil drench reduced the incidence of bacterial wilt about 10–20%, either by applying bacteriophage mixtures immediately before inoculation with the pathogen, or watering the soil several times with such mixtures (Kalpage and De Costa, 2014) ( Table 1 ).…”
Section: Bacteriophage-based Bacterial Wilt Biocontrolmentioning
confidence: 99%
“…Japanese patent with publication number JP2005278513 describes three types of R. solanacearum bacteriophages with lytic activity against the pathogen, which were isolated from soil in Japan. The phages were initially characterized by their genome size and host range, which was assayed against six Japanese strains isolated from tobacco plants, all of them of race 1: M4S, Ps29, and Ps65 of biovar 3, and C319, Ps72, and Ps74 of biovar 4 (Bhunchoth et al, 2015, Supplementary Table S1) and, therefore, all of them belonging to phylotypes I or IV of the former species complex, and presently not R. solanacearum ( Figure 1 ). Biocontrol assays were performed against strain C319 by spraying a phage of type 1 or 2 onto tobacco plants or as a soil conditioner (Yamada and Yamamoto, 2005).…”
Section: Patent Literature On Bacteriophage-based Bacterial Wilt Biocmentioning
confidence: 99%
See 1 more Smart Citation